Sediment core description of GeoB24376-2 recovered during R/V Sonne expedition SO278 at Sartori MV in the Calabrian Arc, Mediterranean Sea - Mechthild Doll; Nele Behrendt; Agathe Eijsink; Gerhard Bohrmann (PANGAEA, 2023)
Sediment cores were collected with a gravity corer and a multi corer from several sites at the Sartori Mud Volcano in the Calabrian accretionary prism (Mediterranean Sea) during R/V Sonne expedition SO278. Here we present core descriptions of GeoB24302-2 (GC01). To capture the sedimentary structure, gravity cores were longitudinally split directly after recovery on board of cruise SO278 and the archive halves were photographed using the smartCIS1600 line scan technique of the MARUM GeoB Core repository at a 500-dpi resolution. To investigate lithological changes in more detail, macroscopic core descriptions are prepared for all cores. The core descriptions provide information about core length, position, water depth, core sections, core image, color, lithology, sedimentary structures and a descriptive text. Sediment color was determined qualitatively using Munsell soil color charts.